Television Cosumption Patterns Among Malaysian Youth: A Systematic Literature Review - Cyril Modili; Haryati Abd Karim; Juliana Abd Wahab (Penerbit UMS, 2022)
This comprehensive review of the literature aims to shed light on Malaysian youth's multi-platform television consumption pattern. This is because television viewing habits have become extremely fluid in recent years. As a result, this review is crucial in order to learn and comprehend what is occurring in contemporary youth consumption patterns, particularly among Malaysian youth. The study employed a systematic evaluation of the literature, which involved the use of pre-defined criteria to select academic publications to be surveyed over a five-year period (early January 2017 to the end of 2021), as well as a qualitative synthesis of the findings. By describing and analysing the titles, abstracts, keywords, and full papers of the 17 articles chosen, and using a revised PRISMA flow, this study arrives at a holistic and systematic assessment of this approach over the last few years to guide future research on youth television consumption patterns, particularly in the local context. The findings indicate a shift in Malaysia's television consumption trends. This study found four themes in Malaysian youth TV consumption patterns: credible and factual TV programmes or content, self-preferences and personal tastes, cognitive and emotional needs, and cultural aspects. However, local circumstances, such as ethnic groups' television consumption patterns, make it considerably more interesting to study because the values ingrained in their cultural identity are distinct from those of mainstream television.